Unphosphorylated SR-like protein Npl3 stimulates RNA polymerase II elongation. - Jessica L Dermody; Jonathan M Dreyfuss; Judit Villén; Babatunde Ogundipe; Steven P Gygi; Peter J Park; Alfred S Ponticelli; Claire L Moore; Stephen Buratowski; Miriam E Bucheli (PLoS ONE)
The production of a functional mRNA is regulated at every step of transcription. An area not well-understood is the transition of RNA polymerase II from elongation to termination. The S. cerevisiae SR-like protein Npl3 functions to negatively regulate transcription termination by antagonizing the binding of polyA/termination proteins to the mRNA. In this study, Npl3 is shown to interact with the CTD and have a direct stimulatory effect on the elongation activity of the polymerase. The interaction is inhibited by phosphorylation of Npl3. In addition, Casein Kinase 2 was found to be required for the phosphorylation of Npl3 and affect its ability to compete against Rna15 (Cleavage Factor I) for binding to polyA signals. Our results suggest that phosphorylation of Npl3 promotes its dissociation from the mRNA/RNAP II, and contributes to the association of the polyA/termination factor Rna15. This work defines a novel role for Npl3 in elongation and its regulation by phosphorylation.